THE IMPLEMENTATION OF READERS' THEATRE TO IMPROVE STUDENTS' SPEAKING: An Action Research in a Private University in Cianjur - Maryani, Yani (2015)
The present study was triggered by the problem with English speaking class when students avoided practice speaking. For English teachers, how to effectively teach speaking has long been a crucial concern issue. Students' practice might be regarded as an essential element to be taken into account for achieving a more successful speaking. Unfortunately, creating an enjoyable learning is a challenge for teachers. One way to arise students' to practice is by using readers' theatre, which will enable them to give more opportunities in speaking. Accordingly, the objective of this study was to investigate the implementation of readers' theatre and students' attitudes toward readers' theatre. Using the design of Classroom Action Research consisted of planning, implementing, observing and reflecting, this research was conducted with twenty students of a private university in Cianjur were selected to be the participants. The data were obtained through classroom observation and questionnaires. Then they were analyzed and reported descriptively. The results of the study revealed that readers' theatre can be used effectively to improve students' English speaking through several ways. The research findings showed students improvement significantly in both two features of speaking, the linguistics: pronunciation, fluency, vocabulary, and paralinguistics: intonation and expression. This research then concluded that 1) Readers' theatre has improved students' speaking by providing stages like reading, rehearsal, and performing stage which facilitated students to speak. The improvement of students' speaking were also assisted by the teacher's role in deciding the reading materials used, managing group activities and providing feedback 2) Students' attitudes toward readers' theatre showed that readers' theatre has positively helped students to be more active in using the language, involving all language skills from listening, speaking, reading and writing